# Bài 41 trang 109 SGK Hình học 10 Nâng cao

##### Hướng dẫn giải

Giả sử: $$M\left( {x;y} \right) \in \left( H \right):\,y = {1 \over x}$$ ta có:

\eqalign{ & M{F_1^2} = {\left( {x + \sqrt 2 } \right)^2} + {\left( {{1 \over x} + \sqrt 2 } \right)^2} \cr&\,\,\,\,\,\,\,\,\,\,\,\, = {x^2} + 2\sqrt 2 .x + 2 + {1 \over {{x^2}}} + 2\sqrt 2 .{1 \over x} + 2 \cr & \,\,\,\,\,\,\,\,\,\,\,\, = \left( {{x^2} + {1 \over {{x^2}}} + 2} \right) + 2\sqrt 2 \left( {x + {1 \over x}} \right) + 2 \cr & \,\,\,\,\,\,\,\,\,\,\,\, = {\left( {{x^2} + {1 \over x}} \right)^2} + 2\left( {x + {1 \over x}} \right).\sqrt 2 + {\left( {\sqrt 2 } \right)^2} \cr & \,\,\,\,\,\,\,\,\,\,\,\, = {\left( {x + {1 \over x} + \sqrt 2 } \right)^2} \cr & M{F_2}^2 = {\left( {x - \sqrt 2 } \right)^2} + {\left( {{1 \over x} - \sqrt 2 } \right)^2} \cr&\,\,\,\,\,\,\,\,\,\,\,\, \;= {\left( {x + {1 \over x}} \right)^2} - 2\sqrt 2 \left( {x + {1 \over x}} \right) + 2 \cr & \,\,\,\,\,\,\,\,\,\,\,\,\, = {\left( {x + {1 \over x} - \sqrt 2 } \right)^2} \cr}

Từ đó suy ra:

+) Với x > 0 thì $$x + {1 \over x} \ge 2$$ (theo bất đẳng thức cô si)

Khi đó: $$M{F_1} = x + {1 \over x} + \sqrt 2 ;M{F_2} = x + {1 \over x} - \sqrt 2$$

$$\Rightarrow M{F_1} - M{F_2} = 2\sqrt 2 .$$

+) Với x < 0 thì $$\left| {x + {1 \over x}} \right| = |x| + {1 \over {|x|}} \ge 2 \Rightarrow x + {1 \over x} \le - 2$$

Khi đó: $$M{F_1} = - x - {1 \over x} - \sqrt 2 ;M{F_2} = - x - {1 \over x} + \sqrt 2$$

$$\Rightarrow M{F_1} - M{F_2} = - 2\sqrt 2$$

Vậy $$|M{F_1} - M{F_2}| = 2\sqrt 2 .$$